2010
DOI: 10.1371/journal.pone.0014204
|View full text |Cite
|
Sign up to set email alerts
|

Power Law versus Exponential State Transition Dynamics: Application to Sleep-Wake Architecture

Abstract: BackgroundDespite the common experience that interrupted sleep has a negative impact on waking function, the features of human sleep-wake architecture that best distinguish sleep continuity versus fragmentation remain elusive. In this regard, there is growing interest in characterizing sleep architecture using models of the temporal dynamics of sleep-wake stage transitions. In humans and other mammals, the state transitions defining sleep and wake bout durations have been described with exponential and power l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 28 publications
4
49
0
Order By: Relevance
“…Missing connections between nearest neighbors k=4 c =1/6 data interpretation [35]. Accurate fitting and validation of power law distributions is an active area of investigation in statistics.…”
Section: Node Degree (K) and Shortest Path Length (L)mentioning
confidence: 99%
See 1 more Smart Citation
“…Missing connections between nearest neighbors k=4 c =1/6 data interpretation [35]. Accurate fitting and validation of power law distributions is an active area of investigation in statistics.…”
Section: Node Degree (K) and Shortest Path Length (L)mentioning
confidence: 99%
“…It is interesting to point out that studies using model systems, such as zebrafish [68], Caenorhabditis elegans [35,69] and Drosophila [70], have started using advanced data mining and analyses that are currently far ahead of mammalian brain studies. The reason for this is probably due to the fact that access to entire and large networks can be achieved in the case of these model organisms because of their small sizes and relative architectural simplicity, while at the same time offering a rich behavioral repertoire [68][69][70][71][72].…”
Section: Statistical Relationshipmentioning
confidence: 99%
“…In some cases, power-law models also performed well. The distinction between multiple exponentials and power laws is not always straightforward, particularly for reduced number of points52. We therefore adopted the principle of parsimony and considered the simplest model that fitted well the experimental curves, thus choosing the exponentials models that best fitted the data.…”
Section: Discussionmentioning
confidence: 99%
“…Even when sample sizes are large, understanding the distribution may not be straightforward. For example, we showed that human sleep stage bout length distributions previously attributed to power-law equations could be equally well described by the sum of 2–3 exponential functions (Chu-Shore et al, 2010). …”
Section: Sample Size As a Surrogate For Distribution Coveragementioning
confidence: 99%